Firms’ real and reporting responses to taxation: A review - Lester, Rebecca; Olbert, Marcel (Journal of Accounting and Economics, 2025)
Taxation is a central economic policy tool, with governments increasingly using tax policy to stimulate local economic growth and also regulate multinational firms. We review the empirical literature that studies the effect of tax policies on firms’ investment, employment, and other real outcomes. Building on the neoclassical theory of corporate taxes and tangible investment, we propose an organizing framework for our review that captures the wide set of tax policies and firm responses examined in accounting research. This framework highlights four dimensions along which accounting scholars contribute to the literature: (i) documenting the role of financial reporting incentives as a moderating factor in firms’ real responses, (ii) studying firms’ reporting versus real responses, (iii) quantifying real effects of tax disclosure regulations, and (iv) improving measurement of firms’ tax status and proxies for investment and employment. We identify open questions for future research and suggest new international, federal, and local settings that may help uncover underlying mechanisms driving observed economic phenomena. Specifically, we encourage scholars to further distinguish firms’ reported and real responses to tax changes and improve measurement of these outcomes, especially in settings related to environmental taxation or settings in which tax avoidance and real outcomes are closely linked.